Merit Piggy Bank in the Digital Economy (Shanti Journal, 2023)
Making merit, especially charity and donation, is enormous in Asian countries, particularly in Thailand, where it has long been systematically incorporated into Thai culture. This study aimed to evaluate the literature on merit-making in the digital economy. A narrative synthesis was employed for this study. The documentary method and content analysis via systematic review were used to analyze the data. Making merit has several benefits such as improving the community, as well as receiving a tax-deductible and reducing a tax burden. The most fruitful form of merit-making is the good deeds accomplished. Apart from donating money to temples, there are other ways to earn merit these days, including volunteering, painting a school building and so on. In the digital age, online merit-making is becoming more popular. These days, donors use applications or online platforms for merit-making so they can keep track online, similar to a merit piggy bank, which may make the donors happy and encourage them to continue donating. It may benefit the government, private agencies, and other organizations in developing an effective strategy to meet the needs and expectations of donors who wish to donate via digital platforms, which may benefit Thai society and beyond.